Knowledge and attitude of general pratictioners towards direct-to-consumer genomic tests: a survey conducted in Italy (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Personal genomic tests (PGT) offered directly-to-consumers (DTC) for complex disease risk assessment have raised several concerns regarding their potential adverse impact. To mitigate worries continuing professional education has been advocated and the central gatekeeper role of family physicians has been highlighted. Nevertheless, to date, only few studies have been published on awareness, involvement and attitudes of  primary healthcare providers on DTC marketing of PGT and, to the best of our knowledge, none in Italy.Methods: An exploratory survey to achieve information about knowledge and attitudes towards DTC-PGT of a selected group of family physicians participating to courses on predictive medicine and public health genomics was conducted. Results: A total amount of 114 partially or fully filled questionnaires was obtained. The majority of the primary care providers (68,4%)  expressed that they are unaware that companies are selling genomic tests directly to consumers, while 31,6% was aware.  In terms of attitudes toward testing 61,1% of the aware respondents deemed the DTC-PGT for chronic complex diseases to be ‘‘not clinically useful.’’  The overwhelming majority of our respondents (95,6%) felt unprepared to answer patients’ questions on DTC-PGT. If only aware respondents are considered this percentage results obviously  lower (86,1%), though still very high. Conclusion: The low percentage of aware respondents suggests that DTC advertising in the realm of genomic testing is still limited in Italy. Should DTC-PGT become more widely used, a comprehensive education program may be necessary to increase family physicians’ awareness and help them discuss testing with their patients.